Alternative energy science and policy - Ammous, Saifedean H. (2011)
This dissertation studies the science and policy-making of alternative energy using biofuels as a case study, primarily examining the instruments that can be used to alleviate the impacts of climate change and their relative efficacy. Three case studies of policy-making on biofuels in the European Union, United States of America and Brazil are presented and discussed. It is found that these policies have had large unintended negative consequences and that they relied on Lifecycle Analysis studies that had concluded that increased biofuels production can help meet economic, energy and environmental goals. A close examination of these Lifecycle Analysis studies reveals that their results are not conclusive. Instead of continuing to attempt to find answers from Lifecycle Analyses, this study suggests an alternative approach: formulating policy based on recognition of the ignorance of real fuel costs and pollution. Policies to combat climate change are classified into two distinct approaches: policies that place controls on the fuels responsible for emissions and policies that target the pollutants themselves. A mathematical model is constructed to compare these two approaches and address the central question of this study: In light of an ignorance of the cost and pollution impacts of different fuels, are policies targeting the pollutants themselves preferable to policies targeting the fuels? It is concluded that in situations where the cost and pollution functions of a fuel are unknown, subsidies, mandates and caps on the fuel might result in increased or decreased greenhouse gas emissions; on the other hand, a tax or cap on carbon dioxide results in the largest decrease possible of greenhouse gas emissions. Further, controls on greenhouse gases are shown to provide incentives for the development and advancement of cleaner alternative energy options, whereas controls on the fuels are shown to provide equal incentives to the development of cleaner and dirtier alternative fuels. This asymmetry in outcomes — regardless of actual cost functions — is the reason why controls on greenhouse gases are deemed favorable to direct fuel subsidies and mandates.